Prevalence Of Cervical Lymph Node Metastasis in Papillary Thyroid Carcinoma: A Prospective Observational Study - Roghani, Adil Shah; Taj, Bakht; Arifullah, Arifullah; Khan, Ali; Hafeez, Muhammad; Khan, Azam (Journal of Neonatal Surgery, 2025)
Background: Usually when papillary thyroid carcinoma presents, it is associated with central and lateral compartment cervical lymph node metastasis. Identifying nodal disease at this stage is critical, as it impacts the surgical management, recurrence risk, and overall prognosis. Knowledge of local prevalence patterns allows better counseling of ENT surgeons and more efficient adoption of surgical management intends to improve oncologic control. Objectives: To determine the frequency and localization of metastasis to cervical lymph nodes in papillary thyroid carcinoma and analyze its association with the central characteristics of the tumors in patients undergoing thyroid surgery. Methodology: this study conducted at Department Of ENT Kabir Medical College, Peshawar from july 2022 to dec 2024. confirmed papillary thyroid carcinoma, doing total thyroidectomy with cervical nodal evolution the patients' preoperative neck CT, shoulders, and suspicious nodal ultrasound were evaluated. Concomitant central and selective lateral compartment dissections were performed. Demographic, tumor size, and nodal involvement data were analyzed using SPSS v24. The Chi-square test was used to access association, and a significance level was used at p <.05. Results: The mean age of the surveyed patients is 41.8 years, with 100 patients sampled, and a standard deviation of 12.6 years.52% of the patients had cervical lymph node metastasis. Central compartment metastasis was present in 38% of patients, and lateral neck metastasis in 14%. Tumours greater than 1cm in size had a higher likelihood of metastasizing to lymph nodes (p=0.021). Also, tumours with more than one focal point were associated with even greater metastatic potential (p=0.033). The youngest age bracket (<40) showed the most aggressive disease with multiple positive lymph nodes. There was no significant correlation between metastatic lymph nodes and patient gender (p=0.287). Conclusion: Most younger patients with papillary thyroid carcinoma and tumours larger than 1cm have cervical lymph node metastasis and central compartment metastasis. It's still most common. The surgical approach and operative plan become more refined through the identification of surgical risk features. Routine central compartment and selective lateral neck assessment will improve disease control and decrease the risk of recurrence...